STRATEGI PROMOSI KAFE RVANG MELALUI INSTAGRAM SEBAGAI UPAYA MENINGKATKAN PENGUNJUNG - Labibah, yusriyyah; S.Sos., M.I.Kom, Mutiah (The Commercium, 2023)
This research is motivated by the increasing number of consumers in a cafe due to promotional activities carried out primarily using Instagram. The reality is that many visitors to the Rvang cafe are dominated by students, this is based on the factor of the need for a place to do assignments, socialize and to unwind. Rvang Cafe chooses Instagram as the main medium for its promotion using the features available both free and paid. This study aims to determine the sales promotion strategy for Rvang cafe via Instagram as an effort to increase consumer buying interest. This research uses a qualitative approach with a case study method. The data obtained was collected through observation, interviews and documentation. The results of this study showed that all informants in this study were Rvang cafe owners, heads of the Rvang cafe marketing division, visitors and also Rvang cafe Instagram followers. The three things include the communication delivered on Instagram, the context or story that is formed, and finally the connection that is built and maintained with customers.